Motivation as Contributing Factor That Impacts Teaching Excellence in Learning - Dipa, Putu Sora (STKIP AGAMA HINDU SINGARAJA, 2021)
Motivation is known as a dynamic and complex thing that provides an important role in learning related to success and failure. There are many factors that greatly influence the quality of teaching motivation. The quality of teaching will be important in the learning process in various ways in education. Education is an important part of the learning process. Commitment and sincerity are things that should be considered in shaping learning patterns to achieve improvement and change. One of the factors that can influence the learning process is motivation. Teaching motivation is usually influenced by a lot of knowledge and experience from someone so that the topic or information provided can be conveyed properly. This article will explain the various factors that can improve the quality of teaching motivation that influences education and learning. Keywords: Education, Learning, Teaching Motivation